Narrative Strategy of Skepticism in N. Gstrein’s Novel “Die englischen Jahre” - E. M. Shastina; Yu. K. Kazakova (Научный диалог)
The novel of the modern Austrian writer Norbert Gstrein (born 1961) “Die englischen Jahre” (1999) is studied as an experience of critical rethinking of the “Austrian identity” in the context of “national identity” (R. Menasse). The relevance of the study is due to the need to comprehend the phenomenon of “Austrian literature” in the second half of the 20th — early 21st centuries. A review of the most significant works of Gstrein is made, it is proved that the novel “The English Years” is a “turning point” in the writer's work. The novelty of the study is seen in the fact that until now Gstrein’s work has not been an object of study in Russian literary criticism. The concept of a narrative strategy is involved in the study, the methods and specifics of the implementation of the “narrative strategy of skepticism”, which actualizes the author’s position to a critical attitude to historical events, are considered. The question is raised about the influence of the “narrative strategy of skepticism” on the reception of the novel. It is proved that the “narrative strategy of skepticism” allows us to trace the changes in the development of the plot of the novel, to identify the features of its poetics, to realize the semantic content of the text when considering the problem of identity on the example of a biographymyth. The methodological basis of the work is the research of foreign and domestic scientists concerning Austrian literature, as well as the nature of the narrative strategy implemented in the genre of the novel.